2018
DOI: 10.1111/imcb.12166
|View full text |Cite
|
Sign up to set email alerts
|

Providence of the CD25+KIR+CD127FOXP3CD8+ T‐cell subset determines the dynamics of tumor immune surveillance

Abstract: CD8 T-regulatory (Treg) cells are emerging as crucial components of immune system. Previous studies have reported the presence of FOXP3 CD8 Treg cells, similar to CD4 Tregs, in cancer patients which produce high levels of the immunosuppressive cytokines, IL10 and TGFβ. At an early stage of tumor development, we have identified a subset of FOXP3 CD8 CD25 KIR CD127 Treg-like cells, which are IFNγ . However, this early-induced CD8 CD25 CD127 T-cell subset is certainly distinct from the IFNγ CD8 T-effector cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that KIR + CD8 + T cells are terminally differentiated cells and display a restricted TCR repertoire ( 9 , 30 ), which is consistent with our findings. Correlations between KIR + CD8 + T cells and tumor immune surveillance ( 31 , 32 ) or chronic viral infections ( 33 , 34 ) have been reported, but the suppressive functions of this population have not been clearly defined previously. We demonstrate the regulatory function of KIR + CD8 + T cells toward pathogenic CD4 + T cells through an in vitro functional assay using PBMCs from CeD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that KIR + CD8 + T cells are terminally differentiated cells and display a restricted TCR repertoire ( 9 , 30 ), which is consistent with our findings. Correlations between KIR + CD8 + T cells and tumor immune surveillance ( 31 , 32 ) or chronic viral infections ( 33 , 34 ) have been reported, but the suppressive functions of this population have not been clearly defined previously. We demonstrate the regulatory function of KIR + CD8 + T cells toward pathogenic CD4 + T cells through an in vitro functional assay using PBMCs from CeD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different reports have evidenced that KIR+ CD8+ T lymphocytes were expanded in patients with tumors due to chronic antigenic stimulation [ 14 ]. However, more recent results described that, at early stages of tumor development, tumor-induced IFNγ-producing KIR+ CD25+ CD127− FOXP3− CD8+ T cells can potentiate immune surveillance by targeting human leukocyte antigen (HLA)-E-restricted CD4+ regulatory T cells (Treg) while leaving the effector T cell population unaffected [ 15 ]. At a later stage of tumor development, when CD4+ Treg cells dominate the tumor-microenvironment, CD4+ Tregs mediate the clonal deletion of these tumor-suppressive KIR+ IFNγ+ CD25+ CD8+ T cells and ensure tumor immune evasion.…”
Section: Introductionmentioning
confidence: 99%
“…At a later stage of tumor development, when CD4+ Treg cells dominate the tumor-microenvironment, CD4+ Tregs mediate the clonal deletion of these tumor-suppressive KIR+ IFNγ+ CD25+ CD8+ T cells and ensure tumor immune evasion. Besides, at later stages of tumor development a FOXP3+ TGFβ+ CD25+ CD127− CD8+ T cell population is expanded [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the role of inflammatory response and infection is postulated in male infertility, and thus also the participation of natural killer (NK) cells and T lymphocytes, perhaps the role of killer immunoglobulin-like receptor (KIR) and its ligands may be presumed. KIR receptors play a central role in the control of NK cell function, but may also be expressed by some lymphocytes [ 7 10 ]. KIR can be of inhibitory or activating function.…”
Section: Introductionmentioning
confidence: 99%